PENGARUH PENGUASAAN TRIGONOMETRI TERHADAP HASIL BELAJAR MATEMATIKA TEKNIK PENGINTEGRALAN DI KELAS XII TEKNIK KOMPUTER JARINGAN (TKJ) SMK NEGERI 1 PADANGSIDIMPUAN - Hasibuan, Sukriadi (JURNAL EDUCATION AND DEVELOPMENT, 2018)
Abstract   This study aims to look at the influence of mastery of trigonometry mathematics learning outcomes in class XII Integration techniques of computer engineering network SMK Negeri 1 Padangsidimpuan. Total population of 124 people. random sampling techniques are drawn as many as 32 ââpeople. Data were collected in 2 ways analyzed first descriptive analysis to see the general picture of the two variables. while the second is inferential statistical analysis using t-test. Mastery of trigonometry has an average value of 67.71, so that in the category of "enough". While the results of learning mathematics  has an average value of 65, 6, were in the category of "pretty" as well. Based on calculations of data obtained tcount = 3.62. While at the level of 95% or 5% error rate, with degrees of freedom (df) = n-2 = 32-2 = 30 obtained ttable =1.70. when compared with tcount , ttable it can be seen that tcount greater than ttable ie 3.62 > 1.70. thus, the alternative hypothesis can be accepted or approved formulated truth. means "there is a significant effect between mastery of trigonometry on the results of studying mathematics in class XII Integration techniques of computer engineering network  SMK Negeri 1 Padangsidimpuan.   Key Word: Mastery Of Trigonometry, Engineering Learning Outcomes Matematka Integration